ASPEK PERLINDUNGAN HUKUM INTERNASIONAL DATA PRIBADI PENGGUNA LAYANAN JEJARING SOSIAL DAN KEWAJIBAN KORPORASI PENYEDIA LAYANAN - Nathaniel, Eliezer; Putra Ariana, I Gede (Kertha Desa; Vol 9 No 7 (2021), 2021)
Tujuan dalam jurnal ini guna mengkaji aturan hukum internasional dan kewajiban Multinational Corporation berhubungan dengan hak privasi, dan perlindungan data pribadi dalam layanan jejaring media sosial. Dalam jurnal ini digunakan metode penelitian hukum normatif dengan menerapkan pendekatan perundang-undangan dan analisis konsep hukum. Hasil kajian dari penelitian jurnal ini menunjukkan bahwa perlindungan hak privasi dan data pribadi diatur didalam berbagai instrument hukum internasional diantaranya International Conuenant on Civil and Political Rights,, Universal Declaration of Human Rights,,European Conuention on Human Rights, CETS No.108, Charter of Fundamental Rights of Europan Union, European General Data Protection Regulation, dan OECD Guidellines on the Protection of Privacy and Trans-border Flows of Personal Data. Multinational Corporate memiliki kewajiban untuk menghormati hak privasi dan perlindungan data pribadi sebagaimana diatur dalam berbagai instrument hukum internasional, kewajiban tersebut dikenakan melalui mekanisme hukum nasional. Kata Kunci: Hak Privasi, Perlindungan Data Pribadi, Hak Asasi Manusia , Kewajiban, korporasi   ABSTRACT The object of this journal is to explore the rules of international law and the obligations of Multinational Corporations concerning the matter of the right to privacy, and protection of personel data in social media services. This journal uses normative legal research method with an approach to legislation and legal concept analysis. The results of the study show that the protection of the right to privacy and personel data is regulated in various international legal instruments including the Universal Declaration of Human Righhts, the International Convention on Civil and Political Rights, the European Convention on Human Rights, CETS No. 108, the European Union Charter of Fundammental Rights, Regulations European General Data Protection, and OECD Guidelines on Privacy Protection and the Cross-Border Flow of Personal Data. Multinational Corporate have an obligation to respect the right to privacy and protection of personel data as regulated in various international legal instruments, these obligations are imposed through national legal mechanisms. Keywords: Keywords: Privacy Rights, Personal Data Protection, Human Rights, Obligations, corporations